ANALISIS SWOT PELAYANAN KESEHATAN RUMAH SAKIT UMUM LIRBOYO KOTA KEDIRI TAHUN 2019 - Reny Nugraheni; Gerardin Ranind Kirana (Jurnal Kesehatan, 2021)
As an effort to improve service quality, Lirboyo Kediri Hospital needs to routinely conduct aSWOT analysis so that it can find out where the internal shortcomings and external challenges areto be minimized, as well as to find out the strengths in internal factors and opportunities inexternal factors as an effort to improve the quality of health services. The purpose of this study wasto analyze the internal and external conditions of Lirboyo Hospital to carry out strategic planning,to improve the quality of hospital services. This study uses descriptive research methods withqualitative methods. The data analysis technique used SWOT analysis. The results of the SWOTanalysis at Lirboyo Hospital obtained a favorable situation by having good opportunities andstrengths so that it can develop the entire potential of the organization to take advantage ofexisting opportunities and can be optimized by minimizing all existing weaknesses and challenges,one of which is by paying attention to human resource management. , namely the addition ofhuman resources to avoid double positions in health workers.